Genotoxicity Evaluation of the Soybean Isoflavone Genistein in Human Papillary Thyroid Cancer Cells. Study of Its Potential Use in Thyroid Cancer Therapy. (17th November 2019) - Ferrari, S. M.; Antonelli, A.; Guidi, P.; Bernardeschi, M.; Scarcelli, V.; Fallahi, P.; Frenzilli, G.
Abstract: Genistein is one of the several known isoflavonic phytoestrogens found in a number of plants, with soybeans and soy products being the primary food source. The aim of the study is to evaluate if genistein is able to exert antineoplastic action in primary human papillary thyroid cancer (PTC) cells. Thyroid tissues were treated with genistein (1–10–50–100 µM). Cell viability, proliferation, DNA primary damage and chromosomal damage were evaluated. An antiproliferative effect was induced by the highest doses of genistein, and such an effect was synergistically enhanced by the cotreatment with the antineoplastic drug sorafenib. Comet assay did not show any genotoxic effect in terms of primary DNA damage at all the times (4 and 24 h) and tested doses. A reduction of hydrogen peroxide-induced DNA primary damage in primary thyrocytes from PTC cells pretreated with genistein was observed. Data suggest that genistein exerts antineoplastic action, does not induce genotoxic effects while reduces oxidative-induced DNA damage in primary thyrocytes from PTC cells, supporting its possible use in therapeutic intervention.